Electrochemically Enabled, Nickel‐Catalyzed Amination. (14th September 2017) - Li, Chao; Kawamata, Yu; Nakamura, Hugh; Vantourout, Julien C.; Liu, Zhiqing; Hou, Qinglong; Bao, Denghui; Starr, Jeremy T.; Chen, Jinshan; Yan, Ming; Baran, Phil S.
Abstract: Along with amide bond formation, Suzuki cross‐coupling, and reductive amination, the Buchwald–Hartwig–Ullmann‐type amination of aryl halides stands as one of the most employed reactions in modern medicinal chemistry. The work herein demonstrates the potential of utilizing electrochemistry to provide a complementary avenue to access such critical bonds using an inexpensive nickel catalyst under mild reaction conditions. Of note is the scalability, functional‐group tolerance, rapid rate, and the ability to employ a variety of aryl donors (Ar−Cl, Ar−Br, Ar−I, Ar−OTf), amine types (primary and secondary), and even alternative X−H donors (alcohols and amides).